2020
DOI: 10.1002/advs.201903511
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalates on Functional Substrates: Concepts, Synergies, and Future Perspectives

Abstract: POMs were studied as heterogeneous acid catalysts and oxidation catalysts. However, this approach is often affected by low specific surface areas, leading to reduced reactivity. [10] Later studies, therefore, pioneered the immobilization of POMs on high surfacearea substrates including porous silica and other metal oxides, [10] as well as more advanced materials such as carbon nanostructures [11] and metal-organic frameworks (MOFs). [9] This strategy can enable maximized exposure of the individual POM molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 155 publications
(154 reference statements)
2
100
0
8
Order By: Relevance
“…To this end, physicochemical and analytical methods for characterisation of structural features and photophysical and electrocatalytical processes are needed. 13,82,83 This review will give a comprehensive overview on characterization techniques for HER and OER photocatalysts addressing the challenge of the complex interplay of processes occurring on several length-and timescales. Given the huge number of articles related to solar driven photocatalysis, this review cannot be exhaustive.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, physicochemical and analytical methods for characterisation of structural features and photophysical and electrocatalytical processes are needed. 13,82,83 This review will give a comprehensive overview on characterization techniques for HER and OER photocatalysts addressing the challenge of the complex interplay of processes occurring on several length-and timescales. Given the huge number of articles related to solar driven photocatalysis, this review cannot be exhaustive.…”
Section: Introductionmentioning
confidence: 99%
“…Another area which holds great potential for POVs is electrocatalysis.H ere,P OVsc ould be used as molecular species in homogeneous solution [20,97,126] or deposited on electrodes for heterogeneous applications. [16,103,118] To date, POVe lectrocatalysis is largely unexplored. Most of the existing studies reported the incorporation of POVs as as olid into carbon paste electrodes,s ot hat analyses of the reactivity and stability of the POVu nder electrochemical conditions is challenging.…”
Section: Emerging Themes In Pov Energy Researchmentioning
confidence: 99%
“…Ein weiterer Bereich, der großes Potential fĂŒrPOVsbirgt, ist die Elektrokatalyse.H ier kçnnten POVs als molekulare Spezies in homogener Lçsung [20,97,126] verwendet oder auf Elektroden fĂŒrh eterogene Anwendungen abgeschieden werden. [16,103,118] Bis heute ist die POV-Elektrokatalyse weit-gehend unerforscht. Die meisten der vorhandenen Studien berichteten ĂŒber den Einbau von POVs als Feststoffe in Kohlenstoffpastenelektroden, sodass ReaktivitĂ€ts-und StabilitĂ€tsanalysen des POVs unter elektrochemischen Bedingungen eine Herausforderung darstellen.…”
Section: Neue Themen Der Pov-energieforschungunclassified
“…Auch hier ist die stabile "Verdrahtung" von POVs auf ElektrodenoberflĂ€chen noch nahezu unerforscht und bildet eine Voraussetzung fĂŒr den Zugang zu Systemen mit hoher Haltbarkeit und technologischer Relevanz. [118] Aufdem Gebiet der Aktivierung kleiner MolekĂŒle haben Kikukawa und Kollegen kĂŒrzlich neue Wege beschritten, indem sie das schalenfçrmige Dodekavanadat [V 12 O 32 ] 4À verwendeten, um elementares Br 2 im zentralen Hohlraum zu binden, was zu einer Br-Br-Bindungspolarisation und signifikanten SelektivitĂ€tsĂ€nderungen in organischen Bromierungsreaktionen fĂŒhrt. [131] In einem verwandten Beispiel zeigten Das und Mitarbeiter, dass POVs CO 2 aus der Luft sequestrieren und als internes CO 3 2À -Templat speichern kçnnen, was zu der Spezies [H 8 V IV 15 O 36 (CO 3 )] 6À fĂŒhrte.…”
Section: Neue Themen Der Pov-energieforschungunclassified